2021
DOI: 10.3390/nu13093033
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Hyperhomocysteinemia Is Not Related to Oxidative Damage or Impaired Vascular Function in Amateur Middle-Aged Runners under Controlled Nutritional Intake

Abstract: To determine the influence of different doses of maximal acute exercise on the kinetics of plasma homocysteine (tHcy) and its relationship with oxidative status and vascular function, nine recreational runners completed a 10 km race (10K) and a marathon (M). Blood samples were collected before (Basal), immediately post-exercise (Post0), and after 24 h (Post24). Nutritional intake was controlled at each sample point. A significant increase in tHcy was observed after both races, higher after M. Basal levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 79 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…Studies in healthy men suggest this effect is transient (41) and dependent on folate status ( i.e. , lower folate status was associated with a greater increase in homocysteine) (42) and does not seem to have an adverse effect on endothelial function (43). Evidence regarding the effect of chronic exercise training or physical activity, however, on homocysteine levels is mixed.…”
Section: Does Micronutrient Composition Modulate Exercise Effects On ...mentioning
confidence: 99%
“…Studies in healthy men suggest this effect is transient (41) and dependent on folate status ( i.e. , lower folate status was associated with a greater increase in homocysteine) (42) and does not seem to have an adverse effect on endothelial function (43). Evidence regarding the effect of chronic exercise training or physical activity, however, on homocysteine levels is mixed.…”
Section: Does Micronutrient Composition Modulate Exercise Effects On ...mentioning
confidence: 99%
“…It has been demonstrated that acute exercise increases Hcy levels in humans, and the magnitude of those elevations depends on prior training preparation [ 130 , 131 ]. Although the basal Hcy serum concentration is lower in people with regular physical activity, up to 47% of athletes develop hyperhomocysteinemia after exercise [ 132 , 133 ].…”
Section: Homocysteine In Horsesmentioning
confidence: 99%
“…It raises concerns for amateur runners participating in triathlons, marathons or ultramarathons. Prolonged post-exercise oxidative stress and hyperhomocysteinemia may lead to vascular endothelial damage in these individuals [ 131 ].…”
Section: Homocysteine In Horsesmentioning
confidence: 99%
See 2 more Smart Citations